How discounts impact IPOs valuation performance and underpricing? A confrontation between warranted and unwarranted discounts - Tizniti, Douaa; Aasri, Mohammed Rachid (Goodwood Publishing, 2021)
Purpose: We investigated the different impacts warranted and unwarranted discounts have on IPOs valuation performance and underpricing. Research methodology: We used multivariate ordinary least squares regression analysis to examine discounts’ determinants, and their impacts on valuation errors and underpricing. We also used bias and accuracy errors to examine valuation performance. Results: We find both final offer price accuracy errors and underpricing negatively related to warranted discounts and positively related to unwarranted discounts. Additionally, warranted discounts are positively related to fair value estimate bias errors, contrarily to unwarranted discounts. Limitations: The relatively small sample size represents our study’s main limitation. Contribution: Unwarranted discounts allow assessing by issuers' underpricing level and underwriters’ sub-optimal efforts and investors' positive returns. Whereas warranted discounts allow issuers to avoid overpricing IPOs and communicate their intrinsic value, investors assess their negative returns, and underwriters reveal their superior qualitative valuation. Regulators can increase after-market efficiency and protect investors by implementing unwarranted discounts’ constraints and warranted discounts’ thresholds.